Clinical Child and Family Psychology Review - Ollendick, Thomas H.; Prinz, Ronald J.; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Editors-in-Chief: Dr. Ronald J. Prinz, University of South Carolina and Dr. Thomas H. Ollendick, Virginia Polytechnic Institute Clinical Child and Family Psychology Review is a quarterly, peer-reviewed journal that provides an international, interdisciplinary forum in which important and new developments in this field are identified and in-depth reviews on current thought and practices are published. The Journal publishes original research reviews, conceptual and theoretical papers, and related work in the broad area of the behavioral sciences that pertains to infants, children, adolescents, and families. Contributions originate from a wide array of disciplines including, but not limited to, psychology (e.g., clinical, community, developmental, family, school), medicine (e.g., family practice, pediatrics, psychiatry), public health, social work, and education. Topical content includes science and application and covers facets of etiology, assessment, description, treatment and intervention, prevention, methodology, and public policy. Submissions are by invitation only and undergo peer review. The Editors, in consultation with the Editorial Board, invite highly qualified experts to contribute original papers on topics of timely interest and significance.
Keywords: Social sciences; Child psychology; School psychology; Child and School Psychology; Social Sciences, general